Epidural anesthesia in repeated cesarean section. - Rolando T. Espín González; Bárbara Lucía Cabezas Poblet; María Antonia Cabezas Poblet; Norma Mur Villar (Medisur)
Background: A spectacular development has been experimented in the Anesthesiology branch in the last few years in the different areas of its competence in which the attendance activity on obstetric patients as well as every aspect related with its adequate practice is of a great importance. Objective: to evaluate the efficacy of epidural anesthesia in repetitive cesarean. Methods: a descriptive retrospective study of a series of cases (112)in which epidural anesthesia in repetitive cesarean was applied from January 2001 to December 2001 in the surgical unit of the Gynecological obstetric service at the University Hospital ¨Dr. Gustavo Aldereguía Lima¨ in Cienfuegos city, Cuba. Some variables such as fixation time of the anesthesia, its duration, transurgical and postsurgical hemodynamic behavior, complications related with the anesthesia, evaluation of the new born baby and, the level of satisfaction of the patients were analyzed. Results: The immediate transurgical and postsurgical hemodynamic behavior was stable predominating normotension and the normal cardiac frequency. The complications related to anesthesia were minimal. The level of satisfaction of the patients was elevated. No alterations in new born babies were presented. As a conclusion, it may be stated that epidural anesthesia in repetitive cesarean is a safety and reliable anesthetic method.